The role of interleukin-10 gene polymorphism (rs 1800872) in the course of herpes zoster in adults - N. V. Onishchenko; Yu. Yu. Riabokon; O. V. Riabokon (Zaporozhye State Medical University, 2018)
Aim. The aim of the work was to determine the role of polymorphism of the interleukin-10 gene (rs 1800872) in the course of herpes zoster in adults. Materials and methods. 50 adult patients with herpes zoster were included into the study. The clinical course of the disease and development of the certain nature of complications were analyzed depending on the genetic polymorphism of the interleukin-10 gene. Statistical data processing was performed with using the formed patient database in the program STATISTICA for Windows 13 (StatSoft Inc., № JPZ804I382130ARCN10-J). Results. It was established that genotype TT of the IL-10 gene (rs 1800872) was recorded in 30 (60.0 %) patients with herpes zoster versus 14 (35.0 %) healthy people from the control group (P = 0.02), which confirmed the significance of the gene polymorphism IL-10 in reactivation of the varicella zoster virus and the manifestation of shingles. Analysis of the polymorphism of the IL-10 gene depending on the clinical form and the severity of shingle showed that genotype TT was significantly more frequently recorded in patients with severe course disease (86.7 % vs. 48.6 %, P = 0.01), however, did not influenced on the formation of certain clinical forms of the disease (P > 0.05). In patients with herpes zoster polymorphism of the IL-10 gene (rs 1800872) influenced the severity of the course of the disease, namely, the TT genotype was associated with a severe course of the disease (P = 0.01) and the development of neurological complications (P = 0.03), which were represented by meningitis (6), Ramsey-Hunt syndrome (3) and the subsequent formation of postherpetic neuralgia (3), as well as of ophthalmic nature (P = 0.0001), which were represented by herpetic blepharoconjunctivitis (16), keratouveitis (3), iridocyclitis (1), subconjunctival hemorrhages (1). Unlike the TT genotype, genotype TG of the IL-10 gene (rs 1800872) was associated with the development of complications with the addition of secondary bacterial microflora (χ2 = 4.5, P = 0.03), the incidence of which did not depend n the severity of herpes zoster (P > 0.05). Conclusions. In patients with herpes zoster, the TT-genotype of the IL-10 gene (rs 1800872) was associated with reactivation of the varicella zoster virus and development of a severe disease course, with formation of neurological (χ2 = 4.75, P = 0.03) and ophthalmic (χ2 = 14.75, P = 0.0001) complications. The TG genotype of the IL-10 gene (rs 1800872) is associated with the development of complications associated with the addition of secondary bacterial microflora (χ2 = 4.5, P = 0.03).